2014
DOI: 10.3944/aott.2014.14.0040
|View full text |Cite
|
Sign up to set email alerts
|

Fourth and fifth carpometacarpal fracture dislocations

Abstract: Early diagnosis and treatment of 4th and 5th CMC dislocation results in good anatomical and functional results. Delayed or incorrect diagnosis of this region causes severe radiological and functional problems. Detailed physical and radiological examination can prevent CMC dislocation from being overlooked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…The average MHOQ score was 98 AE 2 at 1-year follow-up. The good results with early treatment in our conservative group concur with that of Kural et al, 25 who demonstrated that early diagnosis and treatment of fourth and fifth CMC dislocations led to good anatomical and functional results. 26 Because anatomical reduction and fixation are important for CMC joint injuries to obtain a good clinical result, 27 we performed a complete reduction under fluoroscopy to prevent the secondary dislocations.…”
Section: Discussionsupporting
confidence: 91%
“…The average MHOQ score was 98 AE 2 at 1-year follow-up. The good results with early treatment in our conservative group concur with that of Kural et al, 25 who demonstrated that early diagnosis and treatment of fourth and fifth CMC dislocations led to good anatomical and functional results. 26 Because anatomical reduction and fixation are important for CMC joint injuries to obtain a good clinical result, 27 we performed a complete reduction under fluoroscopy to prevent the secondary dislocations.…”
Section: Discussionsupporting
confidence: 91%
“…Good history will be of value in the patients presenting with hand injury. Good quality AP, true lateral and 45 degrees oblique radiographs 6 , 7 should be taken. Woon et al have explained in detail the anatomical reasons for dislocations and the direct and indirect forces acting at the time of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, multiple dorsal CMC dislocations may result in an avulsion fracture of the hamate. Owing to gross swelling that may mask characteristic deformity and its association with other life-threatening conditions, metacarpal base injuries are frequently overlooked or misdiagnosed 8. Furthermore, overlap on the lateral radiograph may obscure delineation of the injury pattern.…”
Section: Discussionmentioning
confidence: 99%